The Influence of Majority Ownership, Profitability, Size of the Board of Directors, and Frequency of Board of Commissioners Meetings on Sustainability Report Disclosure - Trisnawati, Rina; Wardati, Safari Dwi; Putri, Eskasari (Riset Akuntansi dan Keuangan Indonesia, 2022)
Purpose – This study aims to determine the effect of majority ownership, profitability, the size of the directors board, and frequency of board of commissioners meetings on sustainability report disclosure. Design/methodology/approach– The data were tested using multiple linear regression method. The population used are LQ45 companies listed in Indonesian Stock Exchange (IDX) during the years 2017-2020. This study uses purposive sampling method and obtained 80 LQ45 companies for four years of observation. Findings– The results of this study indicated that the size of the directors board has a significant effect on sustainability report disclosure. While majority ownership, profitability, and frequency of board of commissioners meetings have no effect on sustainability report disclosure. Research limitations/implications– The board of directors is the highest element of management that has responsibility for gaining legitimacy. Companies that have a low number of boards of directors will disclose a higher sustainability report. A small board of directors will result in the effectiveness of coordination, communication and control of the CEO and result in participation that has a positive impact on monitoring information disclosure. Practical implications – Companies are expected to pay attention to sustainability reports disclosure because more high demands from stakeholders for non-financial information of each company. Originality/value – This study uses the majority ownership variable where this variable is very rarely used and uses the LQ45 company because previous research has focused on each industrial sector.